2008
DOI: 10.1007/s11240-008-9340-x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous presence of normally non-culturable endophytic bacteria in field shoot-tips of banana and their gradual activation to quiescent cultivable form in tissue cultures

Abstract: Exploring the source of quiescent bacteria in tissue-cultured bananas (Musa sp.) we demonstrate here through a combination of bacterial 16S rDNAbased molecular technique, light microscopy and cultivation-based approaches the ubiquitous presence of endophytic bacteria in the field shoots of different genotypes (Grand Naine, Robusta, Dwarf Cavendish, Ney Poovan and exotic accessions) and their widespread prevalence in apparently clean tissue cultures. A portion of field shoot-tips (10-60%) showed cultivable endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
84
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 37 publications
7
84
1
3
Order By: Relevance
“…The analysis of core Arabidopsis thaliana root microbiome suggested that although various different soil types altered the bacterial endophyte microbiome, actinobacteria were consistently enriched in the endosphere compared with the rhizosphere [4] . Endophytic non-filamentous actinobacteria had been isolated from growing shoot tips of banana [5,6] . Although the healthy-promoting roles of filamentous actinobacteria were widely accepted [7] , the diversity of actinobacteria among the banana root microbiota is still poorly understand.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of core Arabidopsis thaliana root microbiome suggested that although various different soil types altered the bacterial endophyte microbiome, actinobacteria were consistently enriched in the endosphere compared with the rhizosphere [4] . Endophytic non-filamentous actinobacteria had been isolated from growing shoot tips of banana [5,6] . Although the healthy-promoting roles of filamentous actinobacteria were widely accepted [7] , the diversity of actinobacteria among the banana root microbiota is still poorly understand.…”
Section: Introductionmentioning
confidence: 99%
“…However, the greatest evidence of the source of microbial contamination in the multiplication stage relates to endophytic organisms, as these contaminants are not generally eliminated by disinfectant agents because they are hosted inside the vegetal tissues and are protected from the action of surface disinfectants (Thomas, 2007;Scherwinski-Pereira & Costa, 2010). In the case of bananas, the initial explant for in vitro establishment, and therefore, the raw material used for micropropagation, is usually isolated from apical buds, which are protected from contact with the soil by various layers of tissue (immature leaves), which are eliminated during the sterilization process (Oliveira, Costa, & Scherwinski-Pereira, 2008 explants can present high levels of contamination during the establishment and multiplication phases, constituting the major cause of loss of material during micropropagation of the species (Thomas, Swarna, Patil, Prakash, & Rawal, 2008;Thomas & Soly, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, the success of efforts to control microorganisms using substances, in particular those intended for controlling bacteria, the main sources of contamination during large-scale micropropagation, depends on the isolation, identification, and testing of the sensitivity of the bacteria to antibiotics. This is because control of these contaminants is only possible through the use of substances that are within the spectrum of effectiveness against these microorganisms (Thomas et al, 2008;Donnarumma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial organisms, the native habitat of which is air, soil, plants and human, are detected and identified using microbiological, molecular and genetic and biochemical methods both in the long-term passaged plant cultures and plant cultures initiated in vitro [6][7][8][9][10][11][12][13][14]. Latent bacterial infections, defined by many researchers as internal or endophytic, are detected in calli and microplants cultivated in vitro, as well as in various explants such as shoot apices, buds, and meristems [15][16][17][18][19][20][21][22]. Bacterial endophytes performing a number of functions that are important for plants have always been and continue to be the subject of numerous studies [23].…”
Section: Introductionmentioning
confidence: 99%
“…In numerous papers the presence of endophytic microorganisms in in vitro cultivated plant explants was documented by light and electronic microscopy, and using in situ hybridization [15,16,21,[36][37][38]. S o u r c e s o f b a c t e r i a l m i c r o f l o r a. Endophytic bacteria are derived from epiphytic associations of plant rhyzosphere and phytosphere.…”
Section: Introductionmentioning
confidence: 99%